Identificação de áreas com potencialidades de escoamento e retenção hídrica superficial no município de Teofilândia-Ba - Araujo, Angelo Moura (2011)
The present study is based on the identification of potential of areas of flow and retention of water in semi-arid regions, having as study area the small city district of Teofilândia, in the state of Bahia, Brazil. It is also focused in the study of water resources that is related to multiple usages and their importance to the people that depends directly on them. The methodological basis is based on the theoretical discussion and by the use of geoprocessing techniques such as the usage of Digital Terrain Model, in order to prepare thematic maps (aspect, slope, humidity rate, retention, concavity, coast levels), to identification of potential areas for flow and retention of surface flux, as far as the supervised classification of satellite image to identify the main usage of land in the small city area, besides the creation of a database with information about water resources. The concepts discussed in the study deal with the importance of water and hydric resources for the people who live in the northeast of Brazil and the theoretical discussion of environmental models generated from digital image processing methods that suggest an usage of potential areas to the development of projects related to the use of natural resources for the use of the human being in a sustainable and planned way such as the construction of hydric reserves and the indication of favorable areas to agriculture. This research is justified by the importance of identifying potential areas for construction of reserves water and implementation of suitable areas for agricultural development fundamental to the social and economic development of individuals who depend on the use of land for their livelihood. The methods developed in this research constitute important technical-methodological ways that can be used not only as basis to future research in this field of study but also to management of areas for the implementation of social projects with the emphasis on the semi-arid region, in the northeastern Brazilian.